Development of the first edition of African treatment guidelines for common bacterial infections and syndromes - Jessica Craig; Isabel Frost; Aditi Sriram; James Nuttall; Geetanjali Kapoor; Yewande Alimi; Jay Varma (AOSIS, 2021)
Standard treatment guidelines (STGs) are an important tool for ensuring high quality clinical care and prudent antimicrobial use (AMU) and stewardship (AMS). In 2018, African Union (AU) member state representatives recognized the lack of STGs as a barrier to AMS at national and facility levels. Previous research reported that only 17 of 55 (31%) member states had STGs that provided disease- or pathogen-specific antimicrobial treatment recommendations, excluding those that covered only treatment of HIV, malaria, and tuberculosis). The Africa Centres for Disease Control and Prevention convened expert panels to develop first edition antibiotic treatment guidelines for priority infectious diseases and clinical syndromes for pediatric and adult patient populations in Africa. The purpose of the guidelines is to provide healthcare workers with treatment guidance by harmonising existing national STGs, filling gaps where existing STGs are not available, and serving as a model for future guidelines. Two expert panels of 28 total clinicians, pharmacists, and other relevant stakeholders from 14 AU member states representing each continental region convened to develop consensus treatment recommendations for select priority bacterial infections and clinical syndromes. In developing recommendations, the panels considered treatment recommendations from existing STGs, drug availability, clinical experience, and available antimicrobial resistance data. The guidelines underwent an external review process where clinical stakeholders who did not serve on either panel were invited to submit feedback prior to their publication. The guidelines provide empiric antibiotic therapy guidelines - including drug selection, route of administration, formulation, dosage, and therapy duration - and principles of stewardship for 28 bacterial infections or clinical syndromes. The first edition guidelines for the treatment of common infectious diseases and clinical syndromes in Africa aims to improve clinical treatment and antimicrobial stewardship and will serve as a template for future regional guidelines.